O relacionamento de instituições financeiras com os seus clientes segundo percepções de funcionários e clientes - Morais, Ailton José Salazar de (Universidade do Vale do Rio dos Sinos, 2021)
The banking sector has been going through countless changes due to the high level of competitiveness and due to the continuous insertion of technological innovations. In this sense, financial institutions began to invest more and more in technologies to improve processes, products and services on digital platforms. However, if customers are not satisfied with the relationship financial institution, they will migrate to those that offer more attractive advantages, which has been a cause for concern in the banking sector. Given this scenario, the study aimed to describe the perceptions of employees and customers of financial institutions about the influence of the relationship on satisfaction, switching behavior, switching costs, retention and loyalty. The nature of this research presents a qualitative approach and exploratory level, whose research object comprised the financial institutions located in the municipalities of Campo Grande/MS and Cascavel/PR, and semi-structured interviews were applied to five employees and ten customers. The results obtained were analyzed using the content analysis technique. The main findings were: the importance of a close relationship between manager and customer; the need for agility in service and response time to demands; the effectiveness of responses via apps (WhatsApp, for example), phone calls and other social networks or apps; and face-to-face service is still considered one of the important factors to bring the customer and the manager closer at financial institutions.
Keywords: Relacionamento com os clientes; Satisfação; Comportamento de troca; Custos de mudança; Retenção e fidelização; Relationship with customers; Satisfaction; Exchange behavior; Moving costs; Retention and loyalty; ACCNPQ::Ciências Sociais Aplicadas::Administração